Prioritizing Life over Religion in Indonesia’s Covid-19 Fatwas: The Fatwas of NU, Muhammadiyah, and MUI - Hasyim, Syafiq (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
The outbreak of Covid-19 in early 2020 introduced a new angle on the use of Islamic legal argument in Indonesian fatwas. The argument of prioritizing life (ḥifẓ al-ḥayā), rarely considered as a legal argument of fatwa-making, arose during the outbreak of Covid-19. This article seeks to examine the espousal of prioritizing life in Indonesian fatwas in relation to Covid-19. It uncovers the theological, social, and political reasons behind the decision to prioritize the ḥifẓ al-ḥayā. It examines fatwas on Covid-19 issued by three mainstream Islamic organizations NU, Muhammadiyah, and MUI that indicate their reluctance to adopt the argument of prioritizing life in their fatwas. This article uses an interdisciplinary approach combining the interpretation of Islamic legal theory, Islamic jurisprudence, and social sciences analysis. Finally, this article demonstrates how pro-life fatwas, by adapting to the pandemic era by prioritizing life as legal argument, benefits religion in general.